Hidden cities : unmasking and overcoming health inequities in urban settings (WHO GenevaCH, 2010)
Provides information and tools to help governments and local leaders reduce health inequities in their cities. Looks at factors influencing the health of cities including inter alia, governance, natural and built environment, social and economic environment, foo security and quality, and services and health emergency management.
References: p.118 - 126